2016
DOI: 10.1002/qj.2923
|View full text |Cite
|
Sign up to set email alerts
|

Drivers for the deepening of severe European windstorms and their impacts on forecast quality

Abstract: European windstorms are a high-impact weather phenomenon, regularly inflicting substantial damages, both human and economic. This study examines a set of objectively selected intense European windstorms from the 1979-2015 period using re-analysis and forecast products from the European Centre for Medium-Range Weather Forecasts (ECMWF). The storms are first categorized with respect to their diabatic relative to baroclinic contribution to deepening using the pressure tendency equation, and secondly with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…At longer lead times, it systematically underestimates the speed of motion and the depth of the storms. Previous studies also found a slow bias in the track forecasts of extratropical cyclones in general (Froude et al, 2007b) and a negative bias in the intensity forecasts of severe storms only (Pirret et al, 2017). This suggests that the underestimation of the speed of motion is systematic but that of the depth is specific to deep cyclones.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…At longer lead times, it systematically underestimates the speed of motion and the depth of the storms. Previous studies also found a slow bias in the track forecasts of extratropical cyclones in general (Froude et al, 2007b) and a negative bias in the intensity forecasts of severe storms only (Pirret et al, 2017). This suggests that the underestimation of the speed of motion is systematic but that of the depth is specific to deep cyclones.…”
Section: Discussionmentioning
confidence: 83%
“…Froude et al (2007b) also found a slow bias in a systematic evaluation of the track of extratropical cyclones, while Pirret et al (2017) further found a low bias in intensity for severe European storms. This suggests that the speed is systematically underestimated for extratropical cyclones in general, while the intensity is underestimated for deep cyclones only.…”
Section: Ensemble Average and Individual Membersmentioning
confidence: 92%
See 2 more Smart Citations
“…Odell et al (2013) noted large stratospheric geopotential height tendencies during the 1993 Braer storm, the deepest extratropical low on record with 914 hPa minimum surface pressure. A study of 60 severe European windstorms (Pirret et al, 2017) found that in 20 cases the stratosphere contributed 10 or more to their deepening. The pressure tendency equation used in Pirret et al (2017) used the 100 hPa level (∼16 km) as the upper boundary, with the stratospheric contribution being dependent 15 on geopotential height tendencies on this boundary (their dPhi term).…”
Section: Zonal and Vertical Structures Of Rwpsmentioning
confidence: 99%